INTRODUCTION OF THE SYSTEM OF ETHNOPEDAGOPIC MEANS IN THE EDUCATIONAL PROCESS OF PRIMARY SCHOOL (ON THE EXAMPLE OF ETHNOPEDAGOGY OF THE CRIMEA-TATAR PEOPLE) - Асанова, З. (Pedagogy of Higher and Secondary Education, 2011)
The article reveals how best to implement the system of means of ethnopedagogy Crimean Tatar people in the educational process of primary school.